2013
DOI: 10.1021/jp403552k
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Elastic Properties of Heavily B- and N-doped Graphene with Random Impurity Distributions Including Aggregates

Abstract: We focused on elastic properties of B-and N-doped graphene in wide range of concentrations up to 20%. The Young's, bulk and shear moduli and Poisson's ratio have been calculated by means of the density functional theory for a representative set of supercells with disordered impurity patterns including aggregates. In contrast to earlier work, it is demonstrated that doping with nitrogen even strengthens the graphene layers, whereas incorporation of boron induces large structural and morphological changes seen i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 57 publications
2
20
0
Order By: Relevance
“…In our previous work, we studied the mechanical response of nitrogen doped graphene. Interestingly, recent density functional theory study [26] confirms the accuracy of our predictions for mechanical properties of nitrogen doped graphene. We note that the time increment of all simulations was fixed at 0.5 fs.…”
Section: Atomistic Modelingsupporting
confidence: 84%
“…In our previous work, we studied the mechanical response of nitrogen doped graphene. Interestingly, recent density functional theory study [26] confirms the accuracy of our predictions for mechanical properties of nitrogen doped graphene. We note that the time increment of all simulations was fixed at 0.5 fs.…”
Section: Atomistic Modelingsupporting
confidence: 84%
“…4. We calculated the Young's modulus and Poisson's ratio of the graphene sheet using eqn (7) and (8), and the analysis shows a decrease in those elastic physical quantities with an increase in temperature, as shown in Fig. 5(a) and (b), respectively.…”
Section: Finite Temperature Elastic Constantsmentioning
confidence: 99%
“…6 The semimetallic character and unique electronic properties of graphene can be effectively used in high-speed integrated devices, eld effect transistors, gas sensors, exible electronics, supercapacitors, and nano-composites. 7,8 An understanding of the temperature-dependent physical properties of materials is a prerequisite for advanced devicefabrication technology. Several groups have performed atomistic simulations and experimental analyses to calculate the mechanical properties of monolayer graphene.…”
Section: Introductionmentioning
confidence: 99%
“…Hence we obtained surface bulk modulus as defined by us (equation 5) for pure graphene to be equal to 90.24 N/m. The bulk modulus of graphene has earlier been studied by many authors [34][35][36][37]. Reich et al [34] have reported a bulk modulus value of 700GPa and Milowaska et.…”
Section: 11) Energy-volume Curvementioning
confidence: 99%
“…al. [37] has reported a value of 528 GPa for pure graphene. It may be noted that for calculation of volume of the unit cell they take thickness of the cell around 3.4 Å.…”
Section: 11) Energy-volume Curvementioning
confidence: 99%